2013
DOI: 10.1089/jmf.2012.0197
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Composition, Antimicrobial Activities,and Anti–Quorum-Sensing Activities of Ethanol and Ethyl Acetate Extracts fromHypericum connatumLam. (Guttiferae)

Abstract: We studied the polyphenol composition and antioxidant activity of the ethanolic and ethyl acetate extracts of Hypericum connatum (Guttiferae), in addition to their antimicrobial and antiquorum-sensing (AQS) properties. The extracts exhibited a similar polyphenol content and a notable antioxidant activity, which was stronger in the ethanolic extract (EC50=3.2 μg/mL). Ultrahigh-performance liquid chromatography analyses revealed different polyphenol profiles, with rutin and apigen being the main components of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 25 publications
1
15
1
2
Order By: Relevance
“…Chlorogenic acid, like the other cinnamic acids such as caffeic and p-coumaric acids, have particular meaning, being capable of inhibiting LDL oxidation in vitro (Meyer et al, 1998). The presence of the flavonoid rutin, found in the chloroform extract, agrees with the literature that reported this flavonoid in Hypericum brasiliense Choisy, H. perforatum (de Matos Nunes et al, 2010) and in ethanolic extract of H. connatum (Fratianni et al, 2013). Rutin can be easily absorbed and it is found in different tissues, the plasma and the gut, where it affects the growth of some pathogens as demonstrated by the in vitro study of Parkar et al (2008); this compound also acts as a potent metal chelator and a free radical scavenger.…”
Section: Methanol Extract G Gae/mlsupporting
confidence: 86%
See 1 more Smart Citation
“…Chlorogenic acid, like the other cinnamic acids such as caffeic and p-coumaric acids, have particular meaning, being capable of inhibiting LDL oxidation in vitro (Meyer et al, 1998). The presence of the flavonoid rutin, found in the chloroform extract, agrees with the literature that reported this flavonoid in Hypericum brasiliense Choisy, H. perforatum (de Matos Nunes et al, 2010) and in ethanolic extract of H. connatum (Fratianni et al, 2013). Rutin can be easily absorbed and it is found in different tissues, the plasma and the gut, where it affects the growth of some pathogens as demonstrated by the in vitro study of Parkar et al (2008); this compound also acts as a potent metal chelator and a free radical scavenger.…”
Section: Methanol Extract G Gae/mlsupporting
confidence: 86%
“…Unexpectedly, the methanol extract did not exhibit any activity. This is in contrast with previous studies (Dall 'Agnol et al, 2003;Fratianni et al, 2013) which indicated a Table 4 Antimicrobial activity of chloroform, chloroform-methanol 9:1, and methanol extracts of Hypericum perfoliatum.…”
Section: Antimicrobial Activitycontrasting
confidence: 72%
“…The extracts and standards (previously dissolved in methanol) were filtered (0.45  μ m; Waters) before analysis. The analyses were carried at 30°C using a reversed phase column (BEH C 18 , 1.7  μ m, 2.1 100 mm; Waters) following the method of Fratianni et al [17]. The mobile phase consisted of solvent A (7.5 mM acetic acid) and solvent B (acetonitrile) at a flow rate of 250  μ L min −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the activity of H. connatum in the ED test did likely stem from the effects of different compounds. Since polyphenols represent an important component of H. connatum extract (Fratianni et al 2013), in order to evaluate whether these compounds and, more specifically, flavonoids were involved in the observed activity, the effects of some purified flavonoid-enriched fractions were studied on acute ED. A single administration was chosen to study the possible effects of fractions and flavonoids as the experiments with the extract indicated that the acute effect was predictive of a sustained activity after repeated administration.…”
Section: Discussionmentioning
confidence: 99%
“…In Argentina, this plant is used as a cardiac tonic and commercialised under the name cabotoril (Fusco et al 2007). A recent paper by Fratianni et al (2013) describes the biochemical composition of two extracts of H. connatum. Interestingly, these extracts do not contain appreciable amounts of hyperforin but have a high content in polyphenols.…”
Section: Introductionmentioning
confidence: 99%